Laboratory Errors: Types and Frequency in a Tertiary Hospital in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Introduction: In our country, very few of clinical laboratories are running proper quality control program and to the best of our knowledge the preanalytical, analytical, and postanalytical rates of laboratory errors have not been studied extensively. In this study we evaluated the preanalytical, analytical, and postanalytical components of laboratory errors in 3,200 consecutive specimens of a clinical chemistry laboratory in a tertiary hospital for measurement of different analyte concentrations in plasma or serum. Materials and methods: This study was conducted during the period from June 2009 to July 2010 on 3,200 specimens. Analytical errors were detected by repeat analysis of primary sample and by checking quality control. Results: The numbers of preanalytical, analytical and postanalytical errors were 23, 14 and 76 respectively among 32000 tests that we have done on 3,200 specimens (average 10 tests per specimen). Moreover, the causes of errors were analyzed and it was found that preanalytical errors were mostly due to specimen drawn distal to IV infusion, specimen for potassium first drawn into GREY tube (containing sodium fluoride and K EDTA) and then transferred into GREEN tube, long tourniquet time and underfilling of blood collection tube. The analytical errors were due to random and systemic errors and postanalytical errors were due to transcription errors. Conclusion: Results of our study suggest that errors mostly occur in the postanalytical part of testing and they are due to transcription errors. To reduce the laboratory errors we suggest introduction of Laboratory Information System (LIS) of the clinical laboratories connected with Hospital Management System along with stringent quality control program in preanalytical, analytical and postanalytical stages.J Bangladesh Coll Phys Surg 2015; 33(1): 3-6